ECOLOGY IN THE ERA OF GLOBAL CHANGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article represents a thorough analysis of ecology as a scientific discipline and examines the issues related to human activities that lead to the destruction of natural systems. The author explores the consequences of anthropogenic impact, such as deforestation, water pollution, global warming, and the loss of biodiversity. The discussion is based on data from leading global organizations, including the Food and Agriculture Organization (FAO) of the United Nations, the United Nations Environment Programme (UNEP), as well as scientific observations that confirm the threats posed by human activities to the planet. Special attention is given to the consequences of climate change and the depletion of natural resources, which have become not only ecological but also geopolitical problems. Large-scale deforestation, water and air pollution, and the increase in greenhouse gas concentrations — all of these lead to catastrophic changes on Earth, threatening human life and the life of other species. The problems of disappearing water bodies, rising temperatures, and ecosystem degradation require an urgent response from the global community. The article also discusses specific examples, such as the oil spill in the Gulf of Mexico, depletion of water resources due to irrigation-based agriculture, and the geopolitical risks associated with water scarcity, as seen in the case of India and Pakistan. The work emphasizes the need for urgent and coordinated actions, calling for global cooperation, investment in green technologies, a transition to renewable energy sources, and effective management of water resources. An important focus is the formation of a new environmental consciousness, based on solidarity, responsibility, and respect for natural systems. The experience of Singapore is cited as an example of a successful environmental strategy, as, despite lacking its own natural resources, the country has achieved significant success in waste recycling and sustainable use of natural resources. The presented material includes criticism of existing economic and political models that currently contribute to ecological collapse. The author argues that solutions require not only technological innovations but also changes in political and economic governance. Without a comprehensive approach, which includes global cooperation and the sustainable use of natural resources, humanity risks losing the opportunity for harmonious coexistence with nature. The article concludes with a philosophical reflection on the value of nature and the necessity of reassessing the attitude towards it. An important message is the idea that the future of the planet depends on humanity’s ability to find a balance between economic development and the preservation of ecological balance. The author calls for an awareness of the urgency of the problem and for active actions aimed at preventing a potential catastrophe.
Keywords: ecological crisis, humanity and nature, anthropogenic impact, destruction of ecosystems, global warming, environmental pollution, deforestation, loss of biodiversity, sustainable development, climate change.